What are the core features of professional learning community in Chinese preschool teachers’ perspectives: based on grounded theory analysis - Yang, Jia; Zhang, Yifan; Zhou, Yibin; Ji, Yulin (Frontiers in Psychology, 2023)
Introduction: Professional learning community (PLC) has been concerned as an effective way to promote teacher professional development in China. However, PLC must be optimized due to Chinese culture and education system. This study aimed to explore the features of PLC in preschool teachers’ perspectives and provided theoretical basis for PLC localization practice. Methods: Twenty-eight preschool teachers were engaged in a PLC, their interview data and personal reflection diaries were collected and analyzed based on grounded theory analysis. Results and Discussion: Five core features of PLC in teachers’ perspectives were extracted in this study, including a common vision, a read-practice-share flow, continuous reflection, distributed leadership, peer and organizational support. PLC's common vision is to promote teachers’ professional development and children’s development. Teachers learn and reflect in the process of "reading-practice-sharing", peer support and leadership empowerment play an important role in a sustainable PLC.